A comparison between single and multi-camera swimming race analysis systems - Tor, E.; Ball, K.; Pease, D.; Hopkins, W. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
This study compared the reliability of single and multi-camera race analysis systems. Thirteen swimmers were analysed during 25 different swims using two methods of data collection. The parameters selected for further investigation were start time, average swim velocity, average stroke rate, average stroke length and turn time. Mixed modelling was used to compare the mean differences and amount of random error of each system in between swims. Some differences between the means of each parameter exist, however the only meaningful difference was 1st turn time (0.21 s difference). There were also errors associated with both systems particularly with turn times and average velocity. This study reveals that a single camera analysis system is just as accurate as a multicamera system.